PRINSIP KASIH SAYANG, SABAR, DAN HIKMAH DALAM PEMBELAJARAN AL-QUR’AN - Rachmadani (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The teaching of the Qur’an plays a crucial role in shaping the Islamic character of individuals and communities. However, challenges such as insufficient teacher training, limited facilities, and students’ lack of motivation often hinder its effectiveness. This study aims to analyze the principles of patience, compassion, and wisdom in Qur’anic teaching based on Surah Al-Baqarah (2:45), Surah Ali Imran (3:159), and Surah An-Nahl (16:125). Using a library research approach and descriptive analysis, the study highlights the importance of adopting gentle, empathetic, and wise approaches in education. The principle of patience helps address learning challenges, compassion strengthens teacher-student relationships, and wisdom supports the effective delivery of teachings. The findings demonstrate that these principles are effective in creating a conducive learning environment, fostering character development, and enhancing the reception of Qur’anic teachings. This study offers valuable insights for developing teaching methods that meet the needs of modern education.